THE ADSORPTION AND THERMAL-DECOMPOSITION OF PH3 AND NH3 ON GAAS(100) - Singh, N; Murrell, A; Harrison, D; Foord, J (1991)
The adsorption and thermal decomposition of PH3 and NH 3 on the Ga-rich GaAs(100)-(4*1) has been studied using temperature programmed desorption, isotope exchange reactions and high resolution electron energy loss spectroscopy (HREELS). At 120 K PH3 adsorbs molecularly while HREELS and isotope exchange reactions with deuterium suggest that PH2 is the major species present at 300 K. Molecular adsorption is also observed for NH3 at 150 K when both the physisorbed and chemisorbed states are formed. HREELS and isotope exchange reactions show that dissociation of the molecular state to form NH2 occurs when the adsorbed phase is heated.